Asymptotic expansions associated with the jackknife functional. I - Ivanov, O. V.; Bardadym, Т. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We obtain an asymptotic expansion of the functional of the jackknife method, which is used for the estimation of the variance of observational errors in a nonlinear regression model.